Widely non-degenerate nonlinear frequency conversion in cryogenic titanium in-diffused lithium niobate waveguides - Lange, Nina Amelie; Lengeling, Sebastian; Mues, Philipp; Quiring, Viktor; Ridder, Werner; Eigner, Christof; Herrmann, Harald; Silberhorn, Christine; Bartley, Tim (Optics Express)
The titanium in-diffused lithium niobate waveguide platform is well-established for reliable prototyping and packaging of many quantum photonic components at room temperature. Nevertheless, compatibility with certain quantum light sources and superconducting detectors requires operation under cryogenic conditions. We characterize alterations in phase-matching and mode guiding of a non-degenerate spontaneous parametric down-conversion process emitting around 1556 nm and 950 nm, under cryogenic conditions. Despite the effects of pyroelectricity and photorefraction, the spectral properties match our theoretical model. Nevertheless, these effects cause small but significant variations within and between cooling cycles. These measurements provide a first benchmark against which other nonlinear photonic integration platforms, such as thin-film lithium niobate, can be compared.

Students’ use of different material resources for specific purposes in the process of learning mathematics - Stallmeister, Lea; Rezat, Sebastian (Proceedings of the Fifth International Conference on Mathematics Textbook Research and Development)

IPA: Inference Pipeline Adaptation to Achieve High Accuracy and Cost-Efficiency - Ghafouri, Saeid; Razavi, Kamran; Salmani, Mehran; Sanaee, Alireza; Botran, Tania Lorido; Wang, Lin; Doyle, Joseph; Jamshidi, Pooyan (Companion of the 16th ACM/SPEC International Conference on Performance Engineering)

In Situ Alloying of Ti-6Al-7Nb with Copper Using Laser Powder Bed Fusion - Steinmeier, Paul; Hoyer, Kay-Peter; Lopes Dias, Nelson Filipe; Zielke, Reiner; Tillmann, Wolfgang; Schaper, Mirko (Crystals)
Titanium alloys are widely employed for biomedical implants due to their high strength, biocompatibility, and corrosion resistance, yet their lack of intrinsic antibacterial activity remains a major limitation. Incorporating copper, an antibacterial and β-stabilising element, offers a promising strategy to enhance implant performance. This study investigates Ti-6Al-7Nb modified with 1–9 wt.% Cu via in situ alloying during metal-based laser powder bed fusion (PBF-LB/M), with the aim of assessing processability, microstructural evolution, and mechanical properties. Highly dense samples (>99.9%) were produced across all Cu levels, though chemical homogeneity strongly depended on processing parameters. Increasing Cu content promoted β-phase stabilisation, Ti2Cu precipitation, and pronounced grain refinement. Hardness and yield strength increased nearly linearly with Cu addition, while ductility decreased sharply at ≥5 wt.% Cu due to intermetallic formation, hot cracking, and brittle fracture. These results illustrate both the opportunities and constraints of rapid alloy screening via PBF-LB/M. Overall, moderate Cu additions of 1–3 wt.% provide the most favourable balance between mechanical performance, manufacturability, and potential antibacterial functionality. These findings provide a clear guideline for the design of Cu-functionalised titanium implants and demonstrate the efficiency of in situ alloy screening for accelerated materials development.
Keywords: Biomaterial; In Situ Alloying; Titanium; Additive Manufacturing

Regulatory-compliant energy-saving potential for the passing beam of matrix LED headlamps - Fittkau, Niklas; Bußemas, Leon; Malena, Kevin; Gausemeier, Sandra; Trächtler, Ansgar (Proceedings of the 16th International Symposium on Automotive Lighting 2025)
The carbon footprint of modern vehicles and their mechatronic systems is more important than ever. Research by the publicly funded Nalyses project and the HELLA company shows that the headlamps use phase makes a significant contribution to the life cycle footprint taking into account the current electricity mix [1]. Today, functionalities such as adaptive curve light or glare-free high beam ensure comfort and safety by assessing the state of the vehicle and evaluating the driving scenario ahead. In future, this evaluation will be expanded and used to adapt the headlamp to the driving scenario in such a way that as little light as possible is emitted, but as much light as necessary. In order to achieve this goal, an overall evaluation of the regulatory compliant energy saving potential is crucial in a first step and leads to constraints for a dynamic adaption while driving. In this paper, the potential is illustrated by evaluating UNECE Regulation No. 149 and optimizing luminous intensity distributions. Depending on the different resolutions of matrix LED headlamps, this approach can result in a significantly lower luminous flux. On the other hand, the results are point-like distributions that raise the question of whether the regulation still provides for sensible minimum requirements for modern matrix LED headlamps. The results are further presented in a simulated virtual environment with regard to the resulting luminance in different driving scenarios. We then present an approach to integrate regulatory requirements into a control algorithm by setting optimization constraints and saturating the control. Finally, we classify the found luminous intensity distributions qualitatively according to common lighting criteria. In summary, although the investigated minimum distributions are by no means desirable for drivers themselves, they form the basis on which energy-saving distributions for illuminated areas and twilight scenarios could be adaptively controlled in the future.

Islamfeindlichkeit, Muslim:innenfeindlichkeit und antimuslimischer Rassismus: Differenzierende und integrative Ansätze zur Konzeptionalisierung - Diekmann, Isabell (Konfliktdynamik)
Dieser Beitrag fokussiert zum einen die Differenzierung unterschiedlicher Adressat:innen von Feindlichkeit und damit die Frage, inwiefern feindliche Einstellungen gegenüber der Religion des Islams und gegenüber muslimischen Menschen identisch sind. Zum anderen sensibilisiert dieser Beitrag für die unterschiedlichen Ebenen, auf denen Islam-/ Muslim:innenfeindlichkeit als individuelle Einstellungen und antimuslimischer Rassismus als Strukturmerkmal verortet sind. Er zeigt die unterschiedlichen Paradigmen der beiden Forschungstraditionen auf, argumentiert aber auch für ein integratives Verständnis der Konzepte, da die individuelle und strukturelle Ebene eng miteinander verwoben sind. Der Beitrag schließt mit einer Diskussion um theoretische, methodologische und insbesondere handlungspraktische Implikationen im Umgang mit Islam-/ Muslim:innenfeindlichkeit und antimuslimischem Rassismus.

Counting Components of Hurwitz Spaces - Seguin, Beranger Fabrice (Israel Journal of Mathematics)
For a finite group $G$, we describe the asymptotic growth of the number of connected components of Hurwitz spaces of marked $G$-covers (of both the affine and projective lines) whose monodromy classes are constrained in a certain way, as the number of branch points grows to infinity. More precisely, we compute both the exponent and (in many cases) the coefficient of the leading monomial in the count of components containing covers whose monodromy group is a given subgroup of $G$. By the work of Ellenberg, Tran, Venkatesh and Westerland, this asymptotic behavior is related to the distribution of field extensions of~$\mathbb{F}_q(T)$ with Galois group $G$.

Flimsy Spaces - Khanfir, Robin; Seguin, Beranger Fabrice (arXiv:2511.17745)
We study $n$-flimsy spaces, which are the topological spaces that remain connected when removing fewer than $n$ points but become disconnected when removing exactly $n$ points. We show that no such space exists for $n ≥ 3$, and that the compact $2$-flimsy spaces are precisely the dense and order-complete cyclically ordered sets equipped with their order topology. Furthermore, we examine variants of the definition obtained by replacing connectedness by path-connectedness, where paths are either parametrized by $[0,1]$ or by arbitrary compact linear continua.

Digitalisierungsbezogene Kompetenzen im Chemieunterricht fördern – Ein Kurs für Lehrkräfte - Fechner, Sabine; Cornelius, Soraya; Pollmeier, Pascal; Siepmann, Karin; Rubner, Isabel (Digitale Transformation für Schule und Lehrkräfteausbildung gestalten)
Keywords: Digital; Digitalisierung; Künstliche Intelligenz; KI; Messsensoren; Fortbildung; Lehrkräfte; Chemie

Fostering digitalisation-related competences of chemistry teachers - Pollmeier, Pascal; Ditter, David; Weiser, David; Siepmann, Karin; Ditter, Rebecca; Rubner, Isabel; Ponath, Jonas; Fechner, Sabine; Hoffmann, Adrian; Sommer, Katrin; Grandrath, Rebecca; Bohrmann-Linde, Claudia (16th Conference of The European Science Education Research Association (ESERA))
Keywords: Digital; Digitalisierung; Künstliche Intelligenz; KI; Messsensoren; Fortbildung; Lehrkräfte; Chemie

How can students be supported by ChatGPT as a tutor in hands-on chemistry education? - Fox, Marvin Lee; Peeters, Hendrik; Fechner, Sabine (Conference of The European Science Education Research Association (ESERA))
Keywords: Artificial intelligence; education; chemistry

Prompting bei AR-gestütztem Experimentieren im Chemieunterricht - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik e.V. (GDCP))

Harnessing temporal dispersion for integrated pump filtering in spontaneous heralded single-photon generation processes - Brockmeier, Julian; Schapeler, Timon; Lange, Nina Amelie; Höpker, Jan Philipp; Herrmann, Harald; Silberhorn, Christine; Bartley, Tim (New Journal of Physics)

Virtual Reality trifft Künstliche Intelligenz. KI unterstützt bei virtueller Praktikumsvorbereitung - Peeters, Hendrik; Hansel, Jan-Luca; Graute, André; Fischer, Matthias; Weinberger, Christian; Neiske, Iris; Fechner, Sabine (Laborpraxis)

Thematic Working Group 2 - Developing and leading digital learning cultures in schools: the role of leadership - Tan, Seng Chee; Phillips, Mike; Chammon, Jacob; Cochrane, Janet; Eickelmann, Birgit; Kral, Marijke; Medagedara, Peiris; Pangeni, Shesha Kanta; Murtagh, Karen; Kilcoyne, Anthony (Designing Education Ecosystems for the Future: The Role of Digital Technologies. Report of EDUsummIT 2025 (eBook))

Thematic Working Group 4 - Professional digital competence of teachers: leveraging digital technologies to deepen learning - Prestridge, Sarah; Prasse, Doreen; Bescherer, Christine; Bruillard, Eric; Charania, Amina; Drossel, Kerstin; Friesen, Sharon; Ge, Xun; Jacobsen, Michele; Kafyulilo, Ayoub; Morren, Milou; Moynihan, Denis; et al. (Designing Education Ecosystems for the Future: The Role of Digital Technologies. Report of EDUsummIT 2025 (eBook))

Solvolytically debondable adhesive systems – potentials and challenges for repair and recycling - Gilich, Julian; Kroos, Janika; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)
In the context of decarbonization initiatives, the repairability and recyclability of components have become a major concern in various industrial sectors, particularly for resource-intensive components. The development of innovative bonding and debonding processes that must adhere to the stringent mechanical specifications of the manufacturers and facilitate their efficient disassembly is a major issue faced in the implementation of a sustainable circular economy. Although adhesively bonded joints satisfy the stringent requirements for mechanical performance, they present several challenges during the repair and recycling process. Solvolytically debondable epoxy resin adhesives may be employed to overcome this issue. In this study, we aim to conduct an exploratory feasibility study on the application of such chemical debonding mechanisms within an adhesive bond as well as to systematically analyse and evaluate the suitability of such adhesive systems for various applications. To this end, we employed various thermo-analytical methods and quasi-static tensile tests to characterise the mechanical adhesive and joint properties of two solvolytically debondable adhesive systems. Furthermore, we analysed the debondability of the adhesive joints and evaluated their feasibility in an industrial environment. The results indicate considerable application potential for solvolytically debondable adhesives, along with further development steps currently required.

Christologie der Beziehung – Begegnungen mit Frauen im Markusevangelium - Breuer, Saskia; Taschl-Erber, Andrea (Personale Christologie)

Christologie der Beziehung - Begegnungen mit Frauen im Markusevangelium - Breuer, Saskia Rebecca; Taschl-Erber, Andrea (Personal Christology)

Diskriminierungssituationen im Praxissemester aus Sicht von Lehramtsstudierenden - Truong, Ha My; Vogelsang, Christoph
Diskriminierungserfahrungen können sich negativ auf die Kompetenzentwicklung von Schülerinnen und Schülern auswirken, was wiederum Bildungsungerechtigkeit zur Folge haben kann (Hummrich, 2023). Um solchen Dynamiken frühzeitig entgegenzuwirken soll in der Lehrkräfteausbildung, nach den Standards der Kultusministerkonferenz (KMK) auch der reflektierte Umgang mit Diskriminierung gefördert werden: „Die Absolventinnen und Absolventen […] analysieren Konflikte und kennen Methoden der konstruktiven Konfliktbearbeitung sowie des Umgangs mit Gewalt und Diskriminierung“ (KMK, 2019, S.10). Ein wichtiger Bestandteil der universitären Phase ist das Praxissemester (PS), das in NRW ein fünfmonatiges Schulpraktikum umfasst. Obwohl sich bereits einige Studien mit Diskriminierungserfahrungen an Schulen (z.B. Höhl, 2021; Ziemes, 2024) und in der Lehrkräfteausbildung (Fereidooni, 2015) auseinandersetzten, gibt es bislang keine quantitative Studie, die die Perspektive von Lehramtsstudierenden im PS systematisch einbezieht. An der Universität Paderborn wurde daher in einer explorativen Querschnittsbefragung (N=431) erfasst, inwiefern Lehramtsstudierende Diskriminierungssituationen im Praxissemester beobachten und wie sie ihre Kompetenzen im Umgang mit Diskriminierung in der Schule einschätzen. In den Ergebnissen zeigt sich, dass die Studierenden das Differenzmerkmal Migrationshintergrund mit 31% in den beobachteten Fällen als Diskriminierungsgrund nannten. Zudem nahmen sie wahr, dass am häufigsten die Schüler*innen untereinander abwertend über andere Mitschüler*innen sprachen. Dies kam bei 67% der Befragten mindestens einmal im PS vor. Bei den Studierenden selbst haben 11% mindestens einmal im PS Diskriminierung durch Lehrkräfte erfahren und mit 14% wurden sie mindestens einmal von Schüler*innen diskriminiert. Die Studierenden hielten sich aber überwiegend für ausreichend kompetent im Umgang mit Diskriminierungssituationen.